2021
DOI: 10.1021/acs.nanolett.1c00406
|View full text |Cite
|
Sign up to set email alerts
|

Interstitially Mixed Self-Assembled Monolayers Enhance Electrical Stability of Molecular Junctions

Abstract: Electrical breakdown is a critical problem in electronics. In molecular electronics, it becomes more problematic because ultrathin molecular monolayers have delicate and defective structures and exhibit intrinsically low breakdown voltages, which limit device performances. Here, we show that interstitially mixed self-assembled monolayers (imSAMs) remarkably enhance electrical stability of molecular-scale electronic devices without deteriorating function and reliability. The SAM of the sterically bulky matrix (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 41 publications
0
41
0
Order By: Relevance
“…When a reverse bias voltage is applied, all the frontier MPSH orbitals are kept out of the bias window against generating a reverse current in the finite bias. However, it can be imaged that the orbitals can possibly enter the bias window when the negative bias is large enough, leading to the disappearance and even inversion of the rectification, which has been observed by Kong et al in a recent experiment for the SC 11 BIPY diode (this will be discussed in detail below) . From Figure b, it is found that the wavefunctions of these frontier MPSH orbitals are mainly dominated by the BIPY–CC–BIPY group, which leads to stronger couplings with the right electrode, and hence energetically follow the variation of the chemical potential μ R of the right electrode for these MPSH orbitals under bias voltage.…”
Section: Results and Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…When a reverse bias voltage is applied, all the frontier MPSH orbitals are kept out of the bias window against generating a reverse current in the finite bias. However, it can be imaged that the orbitals can possibly enter the bias window when the negative bias is large enough, leading to the disappearance and even inversion of the rectification, which has been observed by Kong et al in a recent experiment for the SC 11 BIPY diode (this will be discussed in detail below) . From Figure b, it is found that the wavefunctions of these frontier MPSH orbitals are mainly dominated by the BIPY–CC–BIPY group, which leads to stronger couplings with the right electrode, and hence energetically follow the variation of the chemical potential μ R of the right electrode for these MPSH orbitals under bias voltage.…”
Section: Results and Discussionmentioning
confidence: 60%
“…However, it can be imaged that the orbitals can possibly enter the bias window when the negative bias is large enough, leading to the disappearance and even inversion of the rectification, which has been observed by Kong et al in a recent experiment for the SC 11 BIPY diode (this will be discussed in detail below). 37 From Figure 3b To further verify the mechanisms for the rectification and significant enhancement in the rectifying performance on Pt electrodes, the bias-dependent electronic transmission spectra for the two single-molecule diodes are inspected and plotted in Figure 4. As shown in Figure 4a, for Ag/SC 11 BIPY−CC− BIPY/Ag, there are a few transmission peaks locating in the energy range from −2.0 to −1.0 eV.…”
Section: Theoretical Model and Computationalmentioning
confidence: 99%
See 1 more Smart Citation
“…The above is just one example where the effect of the template diameter is utilized but a much richer parameter landscape and associated applications will emerge if more parameter ranges are explored. For example, surface charge densities σ circle and σ substrate of the circular template and substrate surface, which were fixed in this study, can be varied over a large range by forming SAMs of mixed molecules in various ratios. , The enriched realms of the parameter space that enable SPP would allow well-controlled single-nanoparticle placement that can be tailored for specific nanoparticles and applications.…”
Section: Resultsmentioning
confidence: 99%
“…Functionalized aromatic systems bearing alkyl chains are important synthons for compounds with applications in materials science, molecular electronics, and catalysis . The self-assembly of organic or organometallic derivatives on metal surfaces often utilizes long alkyl chains, which ensure the alkyl-driven packing of self-assembled monolayers (SAMs) .…”
Section: Introductionmentioning
confidence: 99%